Connectivity of claw-free maximal nontraceable graphs - Dunbar, Jean E.,; Harris, John M.,; Frick, Marietjie,; Van Aardt, Susan, (Utilitas Mathematica, 2011)
It is known that there exists a 2-connected claw-free maximal nontraceable graph of order n for every n ≥ 18. We demonstrate the existence of a 3-connected claw-free maximal nontraceable graph of order n for every n ≥ 60.